Influence Of External and Internal Factors On The Performance Of MSMEs In Indonesia - Nugraha, Fredi Ari; Ahmatang, Ahmatang; Ali, Helmi; Lukiyanto, Kukuh; Tawil, Muhamad Risal (PT. Anagata Sembagi Education, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy, especially in contributing to Gross Domestic Product (GDP) and absorbing labor. However, various internal and external challenges, such as limited access to capital, low financial literacy, and competition with imported products, hinder the growth of MSMEs. The protectionist and debt relief policies implemented by the government aim to protect this sector, but their effectiveness is still questionable. Digitalization is the main strategy in increasing the competitiveness of MSMEs, but its implementation faces infrastructure constraints and low technological literacy. This study uses a qualitative approach with phenomenological methods and case studies to understand the dynamics of MSMEs in Indonesia. Data were collected through in-depth interviews, observations, and document analysis to explore the experiences of MSME actors in facing challenges and adapting to government policies. The results of the study show that synergy between capital, financial literacy, product innovation, and inclusive policies is needed to encourage sustainable MSME growth. Structural reform and increasing investment in high value-added sectors are crucial steps in strengthening the competitiveness of MSMEs in the era of globalization. Therefore, a digitalization-based adaptation strategy and more proactive policy support are needed to ensure the sustainability of MSMEs as a pillar of the national economy. Micro, Small, and Medium Enterprises (MSMEs) play a significant role in the Indonesian economy, especially in contributing to Gross Domestic Product (GDP) and absorbing labor. However, various internal and external challenges, such as limited access to capital, low financial literacy, and competition with imported products, hinder the growth of MSMEs. The protectionist and debt relief policies implemented by the government aim to protect this sector, but their effectiveness is still questionable. Digitalization is the main strategy in increasing the competitiveness of MSMEs, but its implementation faces infrastructure constraints and low technological literacy. This study uses a qualitative approach with phenomenological methods and case studies to understand the dynamics of MSMEs in Indonesia. Data were collected through in-depth interviews, observations, and document analysis to explore the experiences of MSME actors in facing challenges and adapting to government policies. The results of the study show that synergy between capital, financial literacy, product innovation, and inclusive policies is needed to encourage sustainable MSME growth. Structural reform and increasing investment in high value-added sectors are crucial steps in strengthening the competitiveness of MSMEs in the era of globalization. Therefore, a digitalization-based adaptation strategy and more proactive policy support are needed to ensure the sustainability of MSMEs as a pillar of the national economy.